Riding the elevator to extinction: Disjunct arctic-alpine plants of open habitats decline as their more competitive neighbours expand. (August 2022) - Watts, Sarah H.; Mardon, David K.; Mercer, Catherine; Watson, Dan; Cole, Helen; Shaw, Rosalind F.; Jump, Alistair S.
Abstract: Major displacement of arctic-alpine species towards higher elevations and latitudes is anticipated under climate warming. Disjunct plant populations persisting on mountains at the limits of their species' distributions may have a reduced capacity for migration, and therefore offer a particularly sensitive indication of climate change effects. The flora of Scotland's mountains is of international significance because it contains populations of climate relicts which are isolated geographically and located at the rear edge of their global range. We used a unique long-term monitoring dataset recording vegetation change at a mountain outpost site in the Scottish Highlands to identify divergent population trends in ten rare plant species over the last 30 years. Three arctic-alpine specialists ( Sagina nivalis, Sabulina rubella and Saxifraga cernua ) have suffered severe declines of over 50 % of their population size since the mid-1990s, and have been extirpated at their lowest altitude locations. These species are undergoing elevational range contractions and Sagina nivalis is now considered Endangered in Britain. Their open, gravelly snowbed habitats have been affected by vegetation encroachment, landslip and rockfalls. Population changes across all species studied were also significantly related to altitude. Species with stable or increasing population sizes occur at lower altitudes, are taller and have less reliance on sparsely vegetated habitats. These results can be contextualised within broad trends of thermophilization, biotic homogenization, mountain greening and snow cover declines. Our work demonstrates that disjunct low-latitude arctic-alpine plant populations already situated at maximum local elevational gradients could face "mountaintop extinction", with implications for the conservation of regional biodiversity. Highlights: We analyse rare mountain plant monitoring data from Scotland since the mid-1990s. Three arctic-alpine plants declined by over 50 % but lower elevation species expanded. Sagina nivalis is now Endangered in Britain and at its southern European range limit. Population trends related to altitude indicate elevational range contractions. Climate change is causing habitat disturbance and significant vegetation change.